2016
DOI: 10.1051/0004-6361/201628861
|View full text |Cite
|
Sign up to set email alerts
|

Probing dust-obscured star formation in the most massive gamma-ray burst host galaxies

Abstract: Context. As a result of their relation to massive stars, long-duration gamma-ray bursts (GRBs) allow the pinpointing of star formation in galaxies independent of redshift, dust obscuration, or galaxy mass/size, thus providing a unique tool to investigate star formation history over cosmic time. Aims. About half of the optical afterglows of long-duration GRBs are missed owing to dust extinction and are primarily located in the most massive GRB hosts. It is important to investigate the amount of obscured star fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 77 publications
2
49
0
Order By: Relevance
“…The obtained upper limit is SFR < 30 M ⊙ yr −1 . In combination with earlier radio flux measurements of the afterglow, Greiner et al (2016) suggested that the radio emission reported in Stanway et al (2014) was due to the afterglow.…”
Section: Grb 100621amentioning
confidence: 61%
See 1 more Smart Citation
“…The obtained upper limit is SFR < 30 M ⊙ yr −1 . In combination with earlier radio flux measurements of the afterglow, Greiner et al (2016) suggested that the radio emission reported in Stanway et al (2014) was due to the afterglow.…”
Section: Grb 100621amentioning
confidence: 61%
“…The SFR is 20-40 M ⊙ yr −1 based on the Hα line (Elliott et al 2013;Krühler et al 2015) and 66 M ⊙ yr −1 based on SED fitting (Elliott et al 2013). Radio 2.1 GHz observations by Greiner et al (2016) put an upper limit of SFR < 84 M ⊙ yr −1 .…”
Section: Grb 110918amentioning
confidence: 99%
“…In this paper we assume that the radio emission is dominated by star-forming activity. SFRs based on the radio emission are derived by using the equation of Murphy et al (2011) for 1.4-GHz flux densities, which is used in previous studies of LGRB host galaxies (e.g., Perley et al 2015;Greiner et al 2016). Greiner et al (2016) extrapolate flux densities from the rest-frame frequency to 1.4 GHz and provide the equation of radio-derived SFRs as…”
Section: Resultsmentioning
confidence: 99%
“…The inset shows the 16th, 50th, and 84th percentiles of the marginalized star formation history, as well as the time-averaged SFR over the past 100 Myr, corresponding to the timescale of radio emission due to star formation. Right: Radio versus optical SFRs for PTF10hgi (green star), FRB121102 (purple star; assuming a star formation origin for the radio emission; Bassa et al 2017), LGRB hosts (yellow; Perley & Perley 2013;Perley et al 2015;Greiner et al 2016), and SLSN hosts (cyan; Hatsukade et al 2018). Upper limits are shown as open triangles.…”
Section: Origin Of the Radio Emissionmentioning
confidence: 99%